Image Capturing Device with Height Control Using Sixth Sense Technology - K. MalathiSanthoshini, PVN Lakshmi, K. Divya Sai, P.Venkata Siva Kiran (International Journal of Advanced Science and Technology, 2020)
Humans wants to capture the things in their surroundings. Generally, they use mobile phones to capture an image. But there will be certain situations where there might be non-availability of mobiles. In such cases, the image capturing devices based on sixth sense technology can be used. These devices mainly involve the interfacing of camera with a raspberry pi board. The Raspberry Pi micro controller acts as the brain of this device fuelling by python programming. Gestural Interface will enable the camera to capture the images. To meet the requirement while capturing the image, the height of the camera can be adjusted. DC Motor performs the task of changing the height of the camera with the involvement of solenoid and relay. DC motor works on the principle of pneumatic mechanism. The solenoid acts as a push pull device. The captured images can be stored in the memory card attached to the raspberry pi. On internet connectivity they can be sent to the electronic mail.Keywords: Raspberry Pi, Python, Camera, DC Motor, Relay, Solenoid.